Pengaruh Fasilitas Flight Information Display System terhadap Kepuasan Penumpang di Bandar Udara Internasional I Gusti Ngurah Rai Bali: Studi Komparasi pada Terminal Domestik dan Internasional - Rista Putri Veriandani; Irwina Meilani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of Flight Information Display System (FIDS) facilities on passenger satisfaction, measure the magnitude of the effect of FIDS facilities on passenger satisfaction, and analyze the differences in the effect of FIDS facilities on passenger satisfaction between the Domestic Terminal and the International Terminal at I Gusti Ngurah Rai International Airport, Bali. The study was motivated by the important role of FIDS in providing accurate, timely, and easy-to-understand flight information. The different characteristics of domestic and international passengers are expected to result in different effects of FIDS on passenger satisfaction. This study employed a quantitative method with a descriptive-associative approach. Data were collected through questionnaires distributed to 400 respondents, consisting of 200 passengers from the Domestic Terminal and 200 passengers from the International Terminal. The data were analyzed using classical assumption tests, simple linear regression analysis, partial tests (t-test), the coefficient of determination (R²), and the Chow Test. The results indicate that the Flight Information Display System (FIDS) has a positive and significant effect on passenger satisfaction in both the Domestic and International Terminals, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) shows that FIDS explains 74.5% of passenger satisfaction in the Domestic Terminal and 72.8% in the International Terminal. Furthermore, the Chow Test result shows that the calculated F-value of 5.71 is higher than the F-table value of 3.02 (5.71 > 3.02), indicating a significant difference in the effect of FIDS on passenger satisfaction between the Domestic and International Terminals. Therefore, the quality of the Flight Information Display System plays an important role in improving passenger satisfaction, with a greater influence in the Domestic Terminal than in the International Terminal.